WHEN RELIGION AND CULTURE MEET ECONOMY: Socio-legal Factors for the Early Marriages of Muslim Families in Cirebon - Rana, Mohamad; Arifin, Tajul; Kurniawan, Cecep Soleh (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
Indonesian law has established the minimum age for marriage. However, this requirement is in fact largely disregarded by many Muslims in Cirebon. This is evidenced by the high rate of marriage dispensations recorded in Religious Courts and Population Control, Family Planning, Women's Empowerment, and Child Protection Office (DPPKBP3A) data. This study seeks to investigate the sociological cause of early marriages which seemingly contradicts legal efficacy. Data were classified and then analyzed through a socio-legal approach, then concluded. The result of this study shows that early marriage in Cirebon is the end of multi-facets of social burdens, including economic motives, cultural pressure, and religious legality. These factors drive Muslim people in Cirebon to ignore the legal provisions regarding the minimum age for marriage. This ineffectiveness of the state law is also inseparable from the religious views of the community, which recognizes that Islam does not impose the same minimum age requirement as the state.[Hukum Indonesia telah menetapkan usia minimum untuk menikah. Namun, persyaratan ini ternyata banyak diabaikan oleh masyarakat Muslim di Cirebon. Hal ini dibuktikan dengan tingginya angka dispensasi nikah yang tercatat di Pengadilan Agama dan data DPPKBP3A. Penelitian ini memaparkan penyebab sosiologis pernikahan dini yang tampaknya bertentangan dengan efektifitas hukum. Data diklasifikasikan kemudian dianalisis melalui pendekatan sosio-legal, kemudian disimpulkan. Hasil penelitian ini menunjukkan bahwa pernikahan dini merupakan akhir dari berbagai beban sosial, antara lain motif ekonomi, tekanan budaya, hingga legalitas agama. Faktor-faktor inilah yang setidaknya mendorong masyarakat Muslim Cirebon mengabaikan ketentuan hukum negara mengenai usia minimal menikah. Ketidakefektifan hukum negara ini juga tidak terlepas dari pandangan keagamaan masyarakat yang mengakui bahwa Islam tidak menetapkan secara pasti persyaratan usia minimum yang sama dengan negara.]